Managing Commodity-Driven Inflation Risk: The Role of Domestic Price-Setting Policies in ASEAN+3 - Singagerda, Faurani Santi; Sanusi, Anuar; Alam, Iskandar Ali; Hairani, Tuti (International Journal of Economics and Financial Issues, 2025)
This study examined the impact of global oil price volatility on inflation risk in ASEAN+3 economies from 2015 to 2024. Using a Two-Stage Least Squares (2SLS) approach, the analysis introduces the Price-Setting Policy Index (PSPI) as a policy-based instrumental variable to capture domestic interventions, including fuel subsidies, price controls, and tax adjustments. The model utilizes a balanced quarterly panel dataset comprising trade openness, interest rates, FDI, and oil prices. Findings indicated that oil price shocks have only a marginal effect on inflation under current policy frameworks. However, counterfactual simulations suggest stronger inflationary responses in the absence of intervention, highlighting the risk-buffering role of fiscal institutions. The limited significance of traditional monetary controls points to a shift in inflation dynamics toward institutional and policy- driven factors. This study contributes to the literature on inflation risk and financial policy by presenting PSPI as a practical tool for macroeconomic risk management. The framework offers insights for policymakers in emerging markets to design adaptive, context-specific inflation control strategies. Future research may apply nonlinear models and dynamic PSPI indices to better capture evolving risks in volatile energy markets.